The effect of physical therapy and modalities on frozen shoulder patients at Baptist Hospital Batu: a retrospective study - Nadia Ovianti; Nurdiana Adwi Nugrahani (Faculty of Medicine, Universitas Airlangga, 2023)
Introduction: Frozen shoulder was one of top 10 diseases with frequent visits at Baptist Hospital's rehabilitation clinic in 2020. Treatment for this condition includes physical therapy and modalities. This study aims to compare the range of motion and pain scale before and after treatments on frozen shoulder patients in Baptist Hospital Batu. Material and Methods: This is a retrospective study using the data from medical records of patients known to have frozen shoulder who came to outpatient physical rehabilitation clinic at Baptist Hospital, Batu, for at least a month period of treatment. The parameters used are range of motions after interventions, pain scale using VAS, sex, and age. Result: Twenty-two patients were diagnosed with frozen shoulder, 16 patients were included in further analyses, 9 of 16 were women, and the most common age presentation was between 50-60 years. There were improvements in 12 patients being recorded for their shoulder flexion and abduction. The flexion ROM increased from 115 to 156 degrees, while abduction ROM increased from 95 to 144 degrees, on average. About 9 out of 13 patients had decreasing pain scale according to VAS, declining from 5.5 to 4.7. Conclusion: The combination of physical exercises as well as SWD / ultrasound with TENS (transcutaneous electrical nerve stimulation) has a positive impact on the improvement of frozen shoulder. There was an increase in the range of motion of the joint flexion and abduction, and a decrease in pain scores in the majority of the patients after treatment.